2018
DOI: 10.29252/jstnar.22.1.279
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Reservoirs Exploitation with A New Crow Search Algorithm Based on a Multi-Criteria Decision-Making Model

Abstract: Exploitation of dam reservoirs is one of the major problems in the management of water resources. In this research, Crow Search Algorithm (CSA) was used for the first time to manage the operation of reservoirs. Also, the results related to the exploitation of the single-reservoir system of Shahid-Rajaei dam, located in Mazandaran province, northern Iran, which meets the downstream water demands, were compared to those obtained by applying the Particle Swarm and Genetic algorithms. Time reliability, volume reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A case study by Mousavi et al [21] using the crow algorithm for extracting rule curves to manage irrigation on the basis of the potential of crows for finding and hiding foods showed significant decreases in the vulnerability index.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A case study by Mousavi et al [21] using the crow algorithm for extracting rule curves to manage irrigation on the basis of the potential of crows for finding and hiding foods showed significant decreases in the vulnerability index.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The water released from the reservoirs was considered to be a decision variable. The results indicated that this new algorithm, which is based on the social behavior of monkeys, can obtain a global solution with less computation time than the PSOA and GA. For a case study in Iran, Mousvai et al [11] applied the crow algorithm (CA) for irrigation management. This algorithm acts based on the behavior of crows attempting to find food.…”
Section: Introductionmentioning
confidence: 99%
“…Mousavi et al [22] applied the crow algorithm for the extraction of rule curves for the irrigation management for a case study. The algorithm acted based on ability of crows for the finding and hiding of food.…”
Section: Introductionmentioning
confidence: 99%